REPRODUÇÃO INDUZIDA DE LAMBARI, COM DIFERENTES INDUTORES HORMONAIS - SANTOS, Jussara Garrido dos; TAVARES, Tainara Vieira; ORUE, Andrey Makalister Souza; AMARAL, Cristiane Fatima Meldau de Campos; COSTA, Deliane Cristina; WANDERLEY, Alysson Martins (ANAIS DO ENIC, 2023)
-